In vitro increase of mean corpuscular volume difference (dMCV) as a marker for serum hypertonicity in dogs. - Reinhart, Jennifer M.; Yancey, Misty R.; Pohlman, Lisa M.; Schermerhorn, Thomas (My University, 2014)
Spurious increase in erythrocyte mean corpuscular volume (MCV) on automated cell analyzers is a well-characterized lab error in hypertonic patients. A difference between automated and manual MCV (dMCV) greater than 2 fl has been shown to predict hypertonicity in humans. The purpose of this study was to investigate dMCV as a marker for serum hypertonicity in dogs and to examine the relationship between dMCV and three methods of estimating serum tonicity: measured (OsM_M), calculated (OsM_C), and calculated effective (OsM_CE) osmolalities. OsM_C, OsM_CE, and dMCV were calculated from routine blood values and OsM_M was directly measured in 121 dogs. The dMCV of hypertonic dogs was significantly larger than that of normotonic dogs for all three osmolality methods. dMCV predicted hypertonicity as estimated by OsM_M better than it predicted hypertonicity as estimated by OsM_C and OsM_CE. A cutoff of 2.96 fl yielded the best sensitivity (76%) and specificity (71%) for hypertonicity estimated by OsMM.
Keywords: Tonicity; Osmolality; Endocrinology; Metabolism; Sodium